Effectiveness of the implementation of programs in the field of youth policy - Morozova T. D. (Success pedagogy: prospects and opportunities)
Annotation. The article examines the dynamics of the number of young people of the Republic of Crimea by age groups in 2019-2021, reveals the main measures of youth policy, presents measures for the development of the youth program in the Republic of Crimea in 2022.
Keywords: потенциал; молодежь; эффективность; молодежная политика; effectiveness; youth; youth policy; potential; Keywords; целевая ориентация; молодежная программа; профессиональное консультирование; Государственный комитет молодежной политики Республики Крым; Youth program; target orientation; professional counseling; State Committee of Youth Policy of the Republic of Crimea